2016
DOI: 10.1116/1.4941411
|View full text |Cite
|
Sign up to set email alerts
|

Growth, intermixing, and surface phase formation for zinc tin oxide nanolaminates produced by atomic layer deposition

Abstract: Document VersionPublisher's PDF, also known as Version of Record (includes final page, issue and volume numbers) Please check the document version of this publication:• A submitted manuscript is the author's version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…The X-ray photoelectron spectroscopy (XPS) sputter depth profile of the 4 nm SnO2/2 nm ZTO stack in Supplementary Figure 4 shows only partial diffusion of zinc into the tin oxide film, indicating that 4 nm of SnO2 is sufficient to prevent detectable concentrations of zinc from reaching the perovskite. ZTO was deposited by combining SnO2 and ZnO ALD processes in a repeating supercycle consisting of three cycles of SnO2 followed by three cycles of ZnO 43,44 . The parameters for the individual SnO2 and ZnO processes used in the ZTO supercycle are described in Supplementary Tables 1-4.…”
Section: Single-junction Perovskite Solar Cellsmentioning
confidence: 99%
“…The X-ray photoelectron spectroscopy (XPS) sputter depth profile of the 4 nm SnO2/2 nm ZTO stack in Supplementary Figure 4 shows only partial diffusion of zinc into the tin oxide film, indicating that 4 nm of SnO2 is sufficient to prevent detectable concentrations of zinc from reaching the perovskite. ZTO was deposited by combining SnO2 and ZnO ALD processes in a repeating supercycle consisting of three cycles of SnO2 followed by three cycles of ZnO 43,44 . The parameters for the individual SnO2 and ZnO processes used in the ZTO supercycle are described in Supplementary Tables 1-4.…”
Section: Single-junction Perovskite Solar Cellsmentioning
confidence: 99%
“…253,254 An example of these unfavorable effects as a result of large bilayers can be seen where the effect of the bilayer period on the crystallographic phase after annealing at 800 °C was investigated. 253 It was found that large bilayer periods lead to crystalline regions of ZnO and SnO 2 but that films with shorter bilayer periods showed mostly ternary Zn 2 SnO 4 diffraction patterns, the expected phase at this annealing temperature. The results highlight the importance of intermixing, by demonstrating that films with larger bilayer periods can crystallize into distinct phases (resembling Case 1 in Figure 8) rather than a single mixed phase.…”
Section: Intermixing and Phase Formationmentioning
confidence: 99%
“…Hultqvist et al applied the material as a buffer layer in CIGS solar cells, 14,15 Heo et al investigated its use as a channel material in amorphous oxide thin film transistors, 16 and our previous work was motivated by the potential application of ZTO as a transparent conducting oxide (TCO) for solar cells. 7,17 In a previous study, it was reported that ZTO is deposited by ALD with a lower growth rate than would be expected based on the binary growth rates of SnO 2 ALD from TDMASn and H 2 O (0.70 Å/cycle at 150…”
Section: Introductionmentioning
confidence: 99%